2010
DOI: 10.1007/s12011-010-8866-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Arsenic in Scalp Hair of Children and its Correlation with Drinking Water in Exposed Areas of Sindh Pakistan

Abstract: This study was focused on the analysis of arsenic (As) levels in scalp hair of children (age, <10 years) collected from two towns of Khairpur, Pakistan, to evaluate the effects of As-contaminated groundwater. For comparative purposes, scalp hair samples of children were also collected from that area having low levels of As (<10 μg/L) in drinking water. Groundwater and scalp hair samples of children were collected and analyzed by electrothermal atomic absorption spectrometry prior to microwave-assisted acid dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…All the results quoted by Mikulewicz et al (2014) were higher than for group E presented herein. This higher contents of Cr in Control group C2 than in the control group from the quoted study can be accounted for by a different domicile of the individuals under study (Wrocław vs Kraków), among others by air pollution and different composition of drinking water [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the results quoted by Mikulewicz et al (2014) were higher than for group E presented herein. This higher contents of Cr in Control group C2 than in the control group from the quoted study can be accounted for by a different domicile of the individuals under study (Wrocław vs Kraków), among others by air pollution and different composition of drinking water [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other signs and symptoms have also been reported in Bangladesh, i.e., chronic cough, crepitating in the lungs, diabetes mellitus, hypertension, and weakness [30]. Inorganic As in drinking water is generally found in >95% of total As, which can be absorbed easily in the gastrointestinal tract [31]. Approximately 80-100% of inhaled and ingested As is absorbed through the gastrointestinal tract and lungs, but up to 50-70% of the absorbed As is gradually eliminated by methylation in the kidneys through urine.…”
Section: Introductionmentioning
confidence: 99%
“…The referent subjects have no remarkable dermatological symptoms, whereas, exposed subject of both genders have different physiological disorders such as, breathing, gastrointestinal, and skin disorders. Some skin diseases with severe itching on exposure to sunlight have been reported [32,33]. On the other hand, our survey demonstrated that the people of the studied towns have poor socioeconomic status.…”
Section: Resultsmentioning
confidence: 49%
“…The clinical investigations were most decisive to identify the chronic As toxicity, which may induce harmful effects to various organs of the human body [32]. The referent subjects have no remarkable dermatological symptoms, whereas, exposed subject of both genders have different physiological disorders such as, breathing, gastrointestinal, and skin disorders.…”
Section: Resultsmentioning
confidence: 99%